A case of double cancer renal pelvic transitional cell carcinoma and lung squamous cell carcinoma - Kubota, M (Hinyokika kiyo. Acta urologica Japonica, 1988)
A 69-year-old woman was admitted with the chief complaint of gross hematuria and left flank pain ten years after curative right pneumonectomy. Retrograde pyelography showed a filling defect of inferior calyx. Computerized tomography revealed a solid tumor with a low density area arising from the left kidney. The tumor was demonstrated hypovascular by angiography. Left radical nephrectomy by a transabdominal approach was performed. Histological diagnosis was primary transitional cell carcinoma of the left renal pelvis largely replacing the renal parenchyma. Twenty six days after the operation she was discharged. Our case was of double cancer consistent with Warren and Gates criteria and was classified into the nonsimultaneous case according to Moertels criteria. Double cancer of the lung and renal pelvis is very rare and our case seems to be the 7th in the Japanese clinical literature